Pengembangan Media Vitipopo Untuk Meningkatkan Minat Belajar Siswa Pada Pelajaran IPS Kelas IV - Titin Nurliyanti; Dwi Lukitoaji, Beny (Jurnal PGSD Indonesia, 2023)
The research aims to (1) determine the feasibility of the development of interactive video media based on PowerPoint in social science lessons for fourth-grade students at Sonosewu Elementary School, (2) assess the practicality of the VITIPOPO media product, (3) evaluate the effectiveness of the VITIPOPO media in social science lessons for fourth-grade students. The research was conducted at Sonosewu Elementary School, with 27 fourth-grade students as the subjects. This study employed the research and development (R&D) method using Borg & Gall's ten steps, including identifying potential and problems, data collection, product design, design validation, design revision, product testing, product revision, usage testing, product revision, and mass production. The researcher completed up to step 8. Data collection techniques and instruments used expert assessment sheets, media expert sheets, student and teacher response questionnaires, and student interest questionnaires. The results of this development research indicate that (1) the developed product is declared feasible with a percentage obtained from media experts at 87.14% and subject matter experts at 83.64%, (2) the VITIPOPO media development is practical for use in fourth-grade social science lessons with a teacher response rate of 88.00% and a student response rate of 85.18%, (3) the VITIPOPO media development is effective in increasing student interest in learning, as seen from the percentage obtained before and after its use, which is 59.17% and 84.13%, respectively, with an increase of 24.96%. Furthermore, the T-test with a significance value of 0.000 is less than 0.05, concluding that the VITIPOPO media is effective for increasing student interest in learning in fourth grade at Sonosewu Elementary School.